Development of a multifunctional anthropomorphic phantom for performance evaluation in nuclear medicine imaging: preliminary PET/CT validation - Xuesong Su; Zuowei Zou; Yingmao Chen; Hao Hong; Zhiwen Chen; Xuejuan Wang; Jianhua Geng (EJNMMI Physics, 2026)
Abstract Purpose To develop an anthropomorphic phantom that enables the simultaneous evaluation of key performance metrics for nuclear medicine imaging systems and to preliminarily validate its application in PET/CT. Methods The anthropomorphic phantom replicates thoracic and abdominal anatomy, simulating human skeletal structures, lung tissue, soft tissue, and tumors. The phantom is divided into five functional regions: a lung tumor detection region (right lung with spheres), an attenuation and scatter correction assessment region with a non-radioactive compartment (left lung), an abdominal tumor detection region (right abdomen with spheres), a uniform background region (left abdomen), and a spatial resolution assessment region incorporating line sources, centered along the mid-sagittal plane traversing the thoracoabdominal extent. All phantom imaging was performed on a Discovery MI (GE Healthcare) PET/CT scanner using sphere-to-background ratios (SBRs) of approximately 4, 6, 8, and 10, and line-to-background ratios (LBRs) of approximately 200, 500, 1000, and 2000. Spatial resolution was measured using a two-point-source method, including visual assessment and valley-to-peak ratio (VPR) analysis, and a single-point-source method. Lesion detectability was assessed visually and by contrast-to-noise ratio (CNR). Signal-to-noise ratio (SNR), quantitative accuracy (percentage error, PE), image uniformity (IU), and residual error (RE) for attenuation and scatter correction were measured. Additionally, a matched SBR comparison was performed using the NEMA image quality (IQ) phantom. Results As LBR increased from 200 to 2000, the single-point-source spatial resolution improved from approximately 7 mm to 3 mm, whereas the visually determined two-point-source results remained nearly constant around 6 mm. At the fixed 7-mm spacing, VPR decreased with increasing LBR, indicating improved profile separation between adjacent point sources. The 3 mm sphere was detectable in the lung and abdomen at SBRs of ≥ 6 and 10, respectively. For SBRs set to approximately 4, 6, 8, and 10, SNRs measured in the left abdominal uniform region were 20.50, 25.47, 25.19 and 25.75; PE, axial IU, and RE were all < 5%. The additional comparison with the NEMA IQ phantom showed comparable CNR trends, SNR, PE, and IU, but different RE distributions. Conclusions The developed multifunctional anthropomorphic phantom enables the simultaneous evaluation of multiple performance metrics, demonstrating the disparities between different measurement methods under various contrast conditions. These preliminary PET/CT validation results suggest its potential as a practical tool for optimizing clinical imaging protocols, comparing system performances, validating reconstruction algorithms, and supporting routine quality control. Its applicability to other nuclear medicine imaging systems remains to be further validated.